Molecular mechanism of the extended oil accumulation phase contributing to the high seed oil content for the genotype of tung tree (Vernicia fordii) - Lingling Zhang; Pan Wu; Wenying Lu; Shiyou Lü (BMC Plant Biology, 2018)
Abstract Background Oil from seeds of the tung tree (Vernicia fordii) has unique drying properties that are industrially important. We found that the extended oil accumulation period was related to the high seed oil content at maturity among tung tree population. In order to understand the molecular mechanism underlying the high oil content in tung tree seed, Tree H and L were adopted for the further investigation, with seed oil content of about 70 and 45%, respectively. We compared the transcriptomic changes of seed at various times during oil accumulation between the two trees. Results Transcriptomes analysis revealed that many genes involved in glycolysis, fatty acid synthesis, and tri-acyl glyceride assembly still kept high expression in the late period of seed oil accumulation for Tree H only. Many genes in fatty acid degradation pathway were largely up regulated in the late period of seed oil accumulation for Tree L only. Four transcription factors related to fatty acid biosynthesis had different expression pattern in the seed oil accumulation period for the two trees. WRI1 was down regulated and kept the low expression in the late period of seed oil accumulation for the two trees. PII, LEC1 and LEC1-LIKE extended the high expression in the late period of seed oil accumulation in Tree H only. Conclusions The continued accumulation of oil in the late period of seed oil accumulation for Tree H was associated with relatively high expression of the relevant genes in glycolysis, fatty acid synthesis and tri-acyl glyceride assembly. PII, LEC1, and LEC1-LIKE rather than WRI1 should play an important role in the oil continual accumulation in the late period of seed oil accumulation in Tree H. This study provides novel insight into the variation in seed oil content and informs plant breeding strategies to maximize oil yield.